PENGARUH LATIHAN WALL SHOOT DAN CHAIR SHOOT TERHADAP HASIL SHOOTING FREE THROW BOLA BASKET PADA PESERTA EKSTRAKURIKULER PUTRI SMP N 1 JEKULO KUDUS - Muhammad Nasih Choirur Rozaq; Priyanto Priyanto (Unnes Journal of Sport Sciences, 2023)
The background in this study is the lack of accuracy in shooting free throws in basketball games. This study aims to determine the effect of wall shoot and chair shoot exercises on improving basketball free throw shooting results on female extracurricular participants at SMP N 1 Jekulo Kudus. This study uses an experimental method with a two group pre-test post-test design. The population of this study were 30 female extracurricular participants at SMP N 1 Jekulo Kudus. The sampling technique is purposive sampling. The sample of this study was 20 female extracurricular participants at SMP N 1 Jekulo Kudus in 2022. Based on the results of the study, it shows the wall shoot and chair shoot exercises have an effect on increasing the free throw shooting results for female extracurricular members of SMP N 1 Jekulo Kudus in 2022. The conclusion is wall shoot and chair shoot exercises have an effect on increasing free throw shooting results, but are more effective. Exercise using wall shoot exercises in increasing free throw shooting results for female extracurricular members of SMP N 1 Jekulo Kudus in 2022. Suggestions to players to improve shooting results free throws can use a wall shoot practice instead of a chair shoot.